Bicarbonate Natural Mineral Water from Source “F2 Păltiniș” Facilitates Digestion—A Pilot Study - Fabio Pace; Antonio Maria Morselli-Labate; Aladin Abu Issa; Alessandro Zanasi (Gastrointestinal Disorders, 2025)
Background: Dyspeptic symptoms are very common in the general population, with an estimated prevalence of 14% to 41%, and the majority of patients experience symptoms without an organic cause for them (so-called functional dyspepsia). While the pathophysiology of functional dyspepsia remains elusive, the impact of functional dyspepsia on quality of life is detrimental. The treatment involves a change in lifestyle—a healthy diet and physical activity—in combination with pharmacological treatments. However, currently, there is no standard therapy for this condition, although a nutritional approach appears to be feasible and well accepted by patients. In this context, the intake of some mineral water types might be able to play an important role. Objective: The aim of the present study was to evaluate whether the regular intake of bicarbonate natural mineral water (Aqua Carpatica from source “F2 Păltiniș”) is able to positively influence the symptomatic process of dyspepsia, promoting digestion and improving the quality of life of patients. Methods: The patients enrolled in this open-label study had diagnosis of functional dyspepsia formulated in accordance with the Rome III criteria. During the 4-week study, patients had to ingest tap water at 1.5 L/day (wash-out period: 2 weeks), and in the 2-week subsequent period, they had to ingest alkaline natural mineral water at 1.5 L/day. The primary efficacy endpoint of this study includes a statistically significant improvement (p < 0.05) in the “heartburn”, “regurgitation”, and “dyspepsia” subscales and the total Reflux Disease Questionnaire’s (RDQ) score with respect to the effects of alkaline natural mineral water. As secondary endpoints, we considered statistically significant improvements (p < 0.05) in quality-of-life scores (Psychological General Well-Being Index—Short form; PGWB-S), the patient’s self-assessment of the state of efficiency of their digestion, and their sense of post-prandial fullness, as well as the use of antacids. Results: Forty-five patients were enrolled: all were Caucasian and mostly women (25, 55.6% vs. 20 men, 44.4%), and they were aged between 25 and 75 years (50.6 ± 13.5 years; mean ± SD). The results of this preliminary study show a significant improvement in functional dyspepsia symptoms—as assessed via the RDQ—and an improvement in quality of life—as assessed using the PGWB-S score—after the intake of alkaline natural mineral water. Conclusions: This preliminary study provides clinical evidence for a recommendation of alkaline natural mineral water as a symptomatic treatment of dyspepsia.